THE ROLE OF SELF-EFFICACY IN STUDENTS' POETRY WRITING ABILITIES IN ELEMENTARY SCHOOL - Hilmiati; Fitri Hidayanti; Nurshahira Ibrahim (El Midad, 2024)
This research aims to describe [1] the role of self-efficacy in students' ability to write poetry, (2) the difficulties students face in applying self-efficacy in their ability to write poetry, and (3) solutions to overcome students' difficulties in applying self-efficacy in their ability to write poetry in class IV MIN 1 Kota Mataram. This research method uses a qualitative approach with descriptive type and data collection techniques using observation, interviews, and documentation. The results show that the role of self-efficacy in class IV MIN 1 Kota Mataram is as follows: 1) a benchmark for students' activity choices, 2) achieving students' goals, as a driving force in solving problems for students, and 3) as a determinant of students' learning success. The difficulties students face in applying self-efficacy in their ability to write poetry are caused by 1) students' difficulty in determining themes and initial vocabulary to start writing, 2) not understanding the structure of good poetry writing, 3) difficulty in concentrating when doing assigned tasks. The fourth-grade teacher as the class mentor has provided fairly good solutions to overcome students' difficulties in applying self-efficacy in their ability to write poetry, including 1) providing motivation for students to read more diligently by giving specific times for students to read freely, 2) provides examples of existing poetry, and students are required to be more active in the learning process, 3) provides creative teaching methods both in terms of media or when teaching so that students have the initiative from themselves in writing poetry.